Understanding the failed change efforts in the US child welfare system - Lambert, Ariel Audra (Kansas State University, 2021)
This report discusses key issues prevalent in the child welfare system (CWS): child removal, disproportionately targeted communities (e.g., communities of color and LQBTQ+ children), agency loss, child removal, and systematic complacency. I look toward Gidden’s (1984) Structuration Theory (ST) to orient the discussion on the interplay of actor and structure and the relationship to the CWS. Through ST we identify the circumstances that strip actors of their agency and as such, establish how the long history of a firmly held belief within the CWS (e.g., child removal) has led to an intractable, wicked problem. The literature then outlines the history of the CWS, which explains why the issues within the CWS are wicked; it is multiplicities and resistant to change. I end the report with literature that points to one resolution (e.g., family preservation and prevention) and shine light on the impact that this change can have on each of the prevalent issues.
Keywords: Child welfare system; Communication theory